Bupleuri Radix Ameliorates Vascular Inflammation in Human Umbilical Vein Endothelial Cells via Modulation of Tight Junction Protein Expression and Inhibition of Nuclear Factor-κB Activation - Min Yeong Kim; Eun Jin Bang; Yung Hyun Choi; Su Hyun Hong (Journal of Pharmacopuncture)
Objectives: The vascular endothelium plays a central role in the maintenance of vascular homeostasis. Inflammation of vascular endothelial cells has been closely related to the development of a wide range of cardiovascular diseases, including atherosclerosis. Bupleuri Radix (BR) possesses several biological properties, including anticancer, antimicrobial, antiviral, immunomodulatory, and anti-inflammatory properties. Furthermore, it can prevent and cure several diseases, such as the common cold, hepatitis, menoxenia, and hyperlipidemia. However, it is unclear whether BR can regulate vascular endothelial function under inflammatory conditions induced by interleukin-1β (IL-1β), a key proinflammatory cytokine. Therefore, in this study, we aimed to investigate the effect of BR on endothelial cell function using human umbilical vein endothelial cells (HUVECs) with IL-1β-induced inflammation. Methods: The effects of BR on cell migration, angiogenesis, and monocyte adhesion were determined using scratch wound-healing assay, tube-formation assay, cell adhesion assay, fluorescein isothiocyanate-dextran Transwell assay, and transepithelial electrical resistance assay. The expression of tight junction (TJ) protein and adhesion molecules was estimated using western blotting and immunofluorescence assay. The generation of reactive oxygen species was assessed using flow cytometry. Results: BR significantly suppressed the proliferation, migration, and tube-formation ability of IL-1β-stimulated HUVECs, and the expression of adhesion molecules, especially intracellular adhesion molecule-1. BR also regulated TJ protein expression, thereby restoring the transepithelial electrical resistance value to a level comparable to that of IL-1β-treated HUVECs. Moreover, BR decreased the production of intracellular reactive oxygen species and the nuclear translocation of the nuclear factor-kappa-B p65 subunit. Conclusion: These findings revealed for the first time that BR prevents IL-1β-induced inflammation of blood vessel. Therefore, BR has the potential to protect the damage of vascular endothelial cells and prevent the progression of cardiovascular diseases.